Nonalcoholic fatty liver disease and type 2 diabetes: an observational and Mendelian randomization study - Yu, Yuetian; Yu, Yuefeng; Wang, Yuying; Chen, Yi; Wang, Ningjian; Wang, Bin; Lu, Yingli (Frontiers in Endocrinology, 2023)
Introduction: Nonalcoholic fatty liver disease (NAFLD) and type 2 diabetes mellitus (T2DM) are both chronic multi-system diseases that cause tremendous health burden worldwide. Previous epidemiological studies have found a bidirectional relationship between these two diseases; however, its causality remains largely unknown. We aim to examine the causal relationship between NAFLD and T2DM. Methods: The observational analysis included 2099 participants from the SPECT-China study and 502 414 participants from the UK Biobank. Logistic regression and cox regression models were used to examine the bidirectional association between NAFLD and T2DM. Two-sample mendelian randomization (MR) analyses were conducted to investigate the causal effects of the two diseases using summary statistics of genome-wide association studies from the UK Biobank for T2DM and the FinnGen study for NAFLD. Results: During the follow-up, 129 T2DM cases and 263 NAFLD cases were observed in the SPECT-China study, and 30 274 T2DM cases and 4896 NAFLD cases occurred in the UK Biobank cohort. Baseline NAFLD was associated with an increased risk of incident T2DM in both studies (SPECT- China: OR: 1.74 95% confidence interval [CI]:1.12-2.70; UK Biobank: HR: 2.16 95% CI:1.82-2.56), while baseline T2DM was associated with incident NAFLD in the UK Biobank study only (HR: 1.58). Bidirectional MR analysis showed that genetically determined NAFLD was significantly associated with an increased risk of T2DM (OR: 1.003, 95%CI :1.002-1.004, P<0.001); however, there was no evidence of an association between genetically determined T2DM and NAFLD (OR: 28.1, 95%CI: 0.7-1143.0). Conclusions: Our study suggested the causal effect of NAFLD on T2DM development. The lack of a causal association between T2DM and NAFLD warrants further verification.